PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB SISWA KELAS XI SMAM 1 KOTA BENGKULU - Rosi Delta Fitrianah (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This research  aims: 1) To know the effect of teaching  methods to the learning  outcomes of students  in the subjects of Arabic. 2.) The effect of learning motivation to the learning outcomes of students  in the subjects of Arabic. 3.) The influence of teaching  methods and learning motivation toward learning outcomes of students  in the subjects of Arabic. The method used in this research  is the experimental method, the population in this study were students  of class XI SMA Muhammadiyah 1. Me- chanical  Penambilan samples in this study is teknikrandom sampling,  choose  two classes of random sampling from four classes sampled. Class XI IPS was selected  as an experimental class B and  class XI IPS C was chosen  as the control  class. There  are differences  in learning  outcomes Arabic among  students  taught  using learning  methods and  methods suggestopedia eclectic. Evidenced by student  learning  outcomes in the application of an electric method is better  than  the application of the method suggestopedia. Evidenced by student learning outcomes in the application of methods elektiklebih better than the application of the method shown in the ANOVA suggestopedia 1 lines sig = 0.001  <0.05. There are differences between  students  who have high motivation for learning outcomes Arabic better than students  who have low motivation seen in the ANOVA one lane sig =0.252  <0.05. There is the influence of learning with students’ motivation to learn Arabic results it is seen in the second  ANOVAtest track at 4:12 table obtained sig = 0.088  therefore  sigma probability  greater  than 0.05,  the null hypothesis  is accepted